Occurrence of bovine herpesvirus type 4 DNA in Argentinean Holstein cattle from Santiago del Estero, Argentina - Perez, Sandra (2011)
Bovine herpesvirus type 4 (BoHV-4) is a gamma-herpesvirus that has been isolated from apparently asymptomatic animals and from cattle with a variety of clinical signs. The pathogenic role of BoHV-4 remains unclear and it is unknown whether the virus acts as a primary pathogen or whether it facilitates secondary infections After natural or experimental infections, BoHV-4 can establish latency, mainly in cells of the monocyte/macrophage linage. Latent virus can be reactivated after glucocorticoid treatment or by stress factors. In 2007, BoHV-4 was isolated for the first time in Argentina, from samples of bovine abortions. In the present study, we used viral isolation, nested PCR and restriction endonuclease analysis (REA) to investigate the presence of BoHV-4 in bovine leukocytes from a single herd of dairy cattle with reproductive problems. In this work, we demonstrated that BoHV-4 genome is present in the leukocytes of a high proportion (63.4%) of animals, probably in a latent or persistent state. BoHV-4 was isolated from one out of eleven peripheral blood leukocyte (PBL) samples. By REA we demonstrated the existence of genomic variation among the strains circulating in this particular herd. Furthermore, all PBL samples evaluated in this study differed from the American prototype strain, DN 599. Overall, this work demonstrated that BoHV-4 is present in the leukocyte fraction of dairy cattle and that viral strains present in this herd are genetically divergent. Although BoHV-4 was detected in a herd with a background of reproductive disorders, it is not possible to conclude that the virus is the primary responsible for these conditions.